Evaluation of Pro- and Anti-inflammatory Cytokines IL-17 and IL-33 in Autoimmune Hyperthyroidism - Mahdi, Malak Fadel; Abdulkhaliq, Roua Jamal (Trends in Immunotherapy, 2025)
Hyperthyroidism is a medical condition characterized by the excessive production and release of thyroid hormones by the thyroid gland. It has diverse etiologies, clinical manifestations, and treatment options. Among the contributing factors to the development of thyroid disease are cytokines, which influence both the immune system and thyroid follicular cells. Notably, cytokines such as IL-17 and IL-33 play critical roles in autoimmune thyroid diseases by promoting inflammation and modulating immune responses. This study aimed to evaluate the serum levels of IL-17 and IL-33 in Iraqi individuals diagnosed with hyperthyroidism. A total of 60 hyperthyroid patients (21 males and 39 females, aged 17–40 years) and 30 healthy controls (8 males and 22 females) were enrolled. Blood samples were collected, and serum levels of IL-17 and IL-33 were measured using standard ELISA techniques. The results demonstrated a statistically significant increase in IL-17 concentrations in patients with hyperthyroidism (39.480 ± 9.665 ng/L) compared to controls (25.695 ± 4.448 ng/L) (p ≤ 0.01). Similarly, IL-33 levels were significantly elevated in the patient group (1247.745 ± 966.963 ng/L) compared to the control group (32.788 ± 47.741 ng/L) (p ≤ 0.01). These findings suggest a potential role for IL-17 and IL-33 in the immunopathogenesis of hyperthyroidism, highlighting their value as possible biomarkers for disease progression.